COGNITION–CHILDHOOD MALTREATMENT INTERACTIONS IN THE PREDICTION OF ANTIDEPRESSANT OUTCOMES IN MAJOR DEPRESSIVE DISORDER PATIENTS: RESULTS FROM THE iSPOT‐D TRIAL. Issue 8 (27th April 2015) - Miller, Shefali; McTeague, Lisa M.; Gyurak, Anett; Patenaude, Brian; Williams, Leanne M.; Grieve, Stuart M.; Korgaonkar, Mayuresh S.; Etkin, Amit
<x xml:space="preserve">Abstract</x> Background Childhood maltreatment (CM) history has been associated with poor treatment response in major depressive disorder (MDD), but the mechanisms underlying this relationship remain opaque. Dysfunction in the neural circuits for executive cognition is a putative neurobiological consequence of CM that may contribute importantly to adverse clinical outcomes. We used behavioral and neuroimaging measures of executive functioning to assess their contribution to the relationship between CM and antidepressant response in MDD patients. Methods Ninety eight medication‐free MDD outpatients participating in the International Study to Predict Optimized Treatment in Depression were assessed at baseline on behavioral neurocognitive measures and functional magnetic resonance imaging during tasks probing working memory (continuous performance task, CPT) and inhibition (Go/No‐go). Seventy seven patients completed 8 weeks of antidepressant treatment. Baseline behavioral and neuroimaging measures were assessed in relation to CM (history of childhood physical, sexual, and/or emotional abuse) and posttreatment depression outcomes. Results Patients with maltreatment exhibited decreased modulation of right dorsolateral prefrontal cortex (DLPFC) activity during working memory updating on the CPT, and a corresponding impairment in CPT behavioral performance outside the scanner. No between‐group differences were found for imaging or behavior on the Go/No‐go test of inhibition. Greater DLPFC activity during CPT significantly predicted posttreatment symptom improvement in patients without maltreatment, whereas the relationship between DLPFC activity and symptom change was nonsignificant, and in the opposite direction, in patients with maltreatment. Conclusions The effect of CM on prefrontal circuitry involved in executive function is a potential predictor of antidepressant outcomes.